2013
DOI: 10.1155/2013/632121
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Alpha-Melanocyte-Stimulating Hormone Signaling, Viability, and Invasiveness in Melanoma Cells

Abstract: Melanoma is a malignancy with high potential to invasion and treatment resistance. The α-melanocyte-stimulating hormone (α-MSH) signal transduction involving Wnt/β-catenin, c-Kit, and microphthalmia-associated transcription factor (MITF), a known pathway to produce melanin, has been demonstrated as one of cancer stem cell characteristics. This study was aimed to examine the effect of resveratrol, an abundant ingredient of grape and medicinal plants, on α-MSH signaling, viability, and invasiveness in melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…This lead to significantly prolonged animal survival time and reduced melanoma tumor sizes in vivo . This was associated with inhibition of lipopolysaccharide induced tumor migration and decreased markers of EMT [159, 163]. These data support a potential use of mono or combination resveratrol therapy for the management of melanoma.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 71%
See 3 more Smart Citations
“…This lead to significantly prolonged animal survival time and reduced melanoma tumor sizes in vivo . This was associated with inhibition of lipopolysaccharide induced tumor migration and decreased markers of EMT [159, 163]. These data support a potential use of mono or combination resveratrol therapy for the management of melanoma.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 71%
“…Furthermore, upregulation of the α-melanocyte-stimulating hormone (α-MSH) signal transduction pathway involving Wnt/β-catenin, c-kit, and MITF were suppressed by resveratrol [158]. These signaling pathways have well-established roles in the immortality, viability, and invasiveness of melanoma cells [159]. In addition, Lee et al [160] found that resveratrol inhibited STAT3 acetylation, which is markedly increased in melanoma cells when compared to normal melanocytes.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, cytochrome C, and caspase-9 and -3 are released [227, 228]. Furthermore, apurinic/apyrimidinic endonuclease-1/redox factor-1 (APE/Ref-1), a protein enrolled in tumorigenesis, is inhibited [226, 229], resulting in a coordinated decrease in AP-1/JunD protein, MMP-1 and inducible NO (iNO) protein levels [226]. It reduces tumor invasiveness by inhibition of α-melanocyte-stimulating hormone (α-MSH) expression [230].…”
Section: Resveratrolmentioning
confidence: 99%